Innate Immune Cells Are Regulated by Axl in Hypertensive Kidney - Batchu, Sri N. (Am J Pathol, 2018)
The balance between adaptive and innate immunity in kidney damage in salt-dependent hypertension is unclear. We investigated early renal dysfunction and the influence of Axl, a receptor tyrosine kinase, on innate immune response in hypertensive kidney in mice with lymphocyte deficiency (Rag1(−/−)). The data suggest that increased presence of CD11b(+) myeloid cells in the medulla might explain intensified salt and water retention as well as initial hypertensive response in Rag1(−/−) mice. Global deletion of Axl on Rag1(−/−) background reversed kidney dysfunction and accumulation of myeloid cells in the kidney medulla. Chimeric mice that lack Axl in innate immune cells (in the absence of lymphocytes) significantly improved kidney function and abolished early hypertensive response. The bioinformatics analyses of Axl-related gene-gene interaction networks established tissue-specific variation in regulatory pathways. It was confirmed that complement C3 is important for Axl-mediated interactions between myeloid and vascular cells in hypertensive kidney. In summary, innate immunity is crucial for renal dysfunction in early hypertension, and is highly influenced by the presence of Axl.